Semiparametric Accelerated Failure Time Model as a New Approach for Health Science Studies - Mostafa KARIMI; Ardalan SHARIAT (Tehran University of Medical Sciences, 2017)
Semiparametric Accelerated Failure Time Model as a New  Approach for Health Science Studies